The Protection of Human Rights in the Law of Contentious Administrative Jurisdiction in Nicaragua - Navarro Medal, Karlos (2020)
This article presents an analysis of the relationship between human rights, effective judicial protection, and administrative litigation. The fundamental right of every person to access independent courts for justice proclaimed in art. 10 of the Universal Declaration of Human Rights of 1945, was also widely recognized, although in some cases with different formulations, both in European and American law, and in international treaties; and in the Contentious Administrative laws.